Matched and married [large type] - Fuller, Kathleen (Amish mail-order brides novel, 2021)
"Margaret Yoder can't seem to catch a break. Even though she's dedicated to her Amish faith, her wild Rumspringa won't stay in the past, and her mother keeps pressuring her to get married. To placate her mother and get away from former "friends," she decides to return to Birch Creek to visit family - and pretend to find a husband. Like Margaret, Owen Bontrager isn't looking for a spouse, something that's hard to avoid in Birch Creek, where an ad for brides in the local paper has brought a swarm of single women to the thriving town. When he meets Margaret in an unexpected way, they discover they have more in common than they ever expected. In some ways, they are a perfect match. Margaret struggles to keep her goal of avoiding romance in order to focus on being a faithful member of the Amish church, and it doesn't help that she finds Owen intriguing. Knowing they don't have a future together; she returns home and gives in to her mother's insistence that she get married. Can Margaret betray her feelings for Owen and become a dutiful daughter and wife to the man of her mother's choosing? Or will Owen find a way to free Margaret of her past by giving her the future they both are surprised to find they desire?"--